Secondary Metabolites in Plants: Their Role in Modulating the Immune Response to Viral Infections in Hosts - Ismael, Shahad Basil; Ahmed, Maysaa Hamid; Nakeeb, Rowshen Hani Al; Jassim, Tabarak Sabah (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
In order to create biochemical defenses from herbivores, plants generate a wide variety of secondary metabolites. Plants, fungi and bacteria produce metabolites that're essential in fighting off viral infections. These active compounds, like flavonoids, alkaloids and terpenoids have effects by stopping replication blocking viral entry and regulating the immune response of the host. Moreover these secondary metabolites can work as deterrents to lower the spread of viruses through carriers. Their ranging effectiveness makes them potential options, for developing antiviral treatments and medications. Also, several phytophagous insects have developed strong adaptations to these allergens, or by detecting, integrating, as well as analyzing these phytochemicals specifically, they employ these special molecules as their individual defense compounds, particular host-finding signals, or perhaps as sexual pheromones or its precursors. Additionally, insects are pollinators and frequently directed by certain flower scents. The ecological relevance of these secondary metabolites of plants within the wide range of virus and insect-plant relationships is shown throughout this article.